From Fear to Fluency: How Anxiety Influences ESL Students’ Classroom Performance - Empuerto, Caryl Joy I.; Luces, Alyssa Marie D.; Hernandez, Anna Bhea Y.; Montero, Isaac G.; Palmon, Hyra Lecka F.; Orbista, John R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This quantitative study examined how foreign language anxiety influenced classroom participation among English as a Second Language (ESL) students at Aklan State University, Banga Campus. Utilizing the Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz, Horwitz, and Cope (1986), the research investigated four primary components of anxiety: communication apprehension, test anxiety, fear of negative evaluation, and anxiety about comprehension. A total of 43 first- and second-year BSEd English students participated in the study. Data were collected through standardized Likert-scale questionnaires and participation checklists, and analyzed using SPSS Version 16 to determine correlations between anxiety levels and student engagement. Findings revealed that most participants experienced moderate to high levels of anxiety, with classroom participation and fear of negative evaluation being the most significant factors affecting their participation. A statistically significant inverse relationship was found between anxiety and student participation—higher anxiety levels were associated with reduced classroom engagement. Communication apprehension and fear of negative evaluation emerged as the strongest predictors of avoidance behaviors, such as reluctance to speak in class or volunteer responses. Although comprehension-related anxiety was less prominent, it still contributed to overall emotional discomfort. The study concluded that psychological barriers—rather than linguistic ability alone—played a central role in limiting student participation in ESL classrooms. The results underscored the need for emotionally supportive teaching strategies and classroom environments that minimize anxiety and encourage active participation. These findings offer critical implications for educators, administrators, and researchers aiming to enhance ESL instruction and reduce affective obstacles to language acquisition.